Peningkatan Literasi Digital Siswa melalui Kuis Berbasis Aplikasi Quizizz Oleh Kampus Mengajar Angkatan 6 di SMPS Muhammadiyah 55 Kandangan - Muhammad Farhan; Darwin Nathaniel; Fery Padli Pratama; Victor Asido Elyakim P (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2024)
This community service activity aims to improve student digital literacy at SMPS Muhammadiyah 55 Kandangan through the implementation of Quizizz application-based quizzes. Digital literacy is increasingly important in the current era of digitalization, especially in the learning process. Through the use of educational technology such as Quizizz, it is hoped that students can get used to using technology in an interactive and fun way. The method used in this service is counseling and training to students on the use of the Quizizz application and assistance during the implementation of quizzes. This activity involves 7th, 8th, and 9th grade students who take part in interactive learning sessions using Chromebook and laptop devices. The research design used a one group pretest-posttest model to evaluate the effectiveness of the activity. The results showed a significant improvement in students' digital literacy after using the Quizizz application, with more than 70% of students experiencing an increase in posttest scores compared to the pretest. The use of this game-based application succeeded in creating a competitive and fun learning atmosphere, which had a positive impact on student motivation. However, obstacles such as limited devices and internet access are challenges that need to be overcome so that technology-based learning can run more optimally.